First detection of Trichinella pseudospiralis infection in raccoon (Procyon lotor) in Central Europe - Cybulska, Aleksandra; Skopek, Rafał; Kornacka, Aleksandra; Popiołek, Marcin; Piróg, Agnieszka; Laskowski, Zdzisław; Moskwa, Bożena (Veterinary parasitology, 2018)
The raccoon (Procyon lotor) is a North American carnivore introduced to Europe in the 20th Century. Raccoons are believed to be the potential hosts of many parasites, or to be involved in their transmission to other animals. Nematodes of the genus Trichinella can infect many carnivorous and omnivorous animals worldwide. The aim of the present study was to determine the occurrence of Trichinella spp. infection in raccoons in Central Europe. Muscle samples were collected from various regions of Poland, the Czech Republic and Germany during the years 2012-2016. The larvae of Trichinella spp. were detected in 11 raccoons, and these were identified as T. spiralis and T. pseudospiralis by multiplex PCR (89.9% and 9.1%, respectively). No mixed infection was observed. This is the first report describing the occurrence of T. spiralis and T. pseudospiralis in P. lotor in Central Europe. Our findings also show that the raccoon population acts as a reservoir of Trichinella pseudospiralis.
Keywords: Poland; Trichinellosis; Trichinella; Trichinella pseudospiralis; Prevalence; Procyon lotor; Sylvatic cycle; Raccoon; Česká republika; prevalence; Německo; Raccoons; Czech Republic; Polsko; mývalové; trichinelóza; zvířata; Germany; larva; Larva; Animals